A study on the impact of e- banking on customer satisfaction in India - ROBERT. P, WILLIAM; GOWTHAMAN, DEVI PREETHA (The journal of contemporary issues in business and government, 2020)
Presently the financial service sector in banking industry is undergoing various innovation.The paper titled is to determine the impact of E-banking on Customer Satisfaction. The objective of this study is to determine the E-banking factors on Customer Satisfaction. Descriptive research design is used in this study.The data is collected on probability basis from 117 respondents and is analyzed with the SPSS tool. The collected data were classified, tabulated and analyzed with statistical tools Frequency analysis, Mean analysis, Independent sample Test,One way Anova and Regression analysis. The result showed that majority of the respondents were female and of age is between 18-25 years who uses E- Banking. Findings of regression analysis is the factors of E- banking is influencing the Customer satisfaction.There is no significant difference between Gender,Marital status and Type of account with respect to perception of E-Banking and Customer satisfaction and there is no significant difference among Age level,Education,Place of Residence,Occupation,Reason with respect to use, Transaction and Encourage to use E-banking with respect to perception of E-banking and Customer satisfaction.